Modulation of TRP ion channels by venomous toxins - Siemens, Jan; Hanack, Christina (Mammalian Transient Receptor Potential (TRP) Cation Channels, 2014)
Venoms are evolutionarily fine-tuned mixtures of small molecules, peptides, and proteins—referred to as toxins—that have evolved to specifically modulate and interfere with the function of diverse molecular targets within the envenomated animal. Many of the identified toxin targets are membrane receptors and ion channels. Due to their high specificity, toxins have emerged as an invaluable tool set for the molecular characterization of ion channels, and a selected group of toxins even have been developed into therapeutics. More recently, TRP ion channels have been included as targets for venomous toxins. In particular, a number of apparently unrelated peptide toxins target the capsaicin receptor TRPV1 to produce inflammatory pain. These toxins have turned out to be invaluable for structural and functional characterizations of the capsaicin receptor. If toxins will serve similar roles for other TRP ion channels, only future will tell.